Detection of arenization foci in the Guariroba river watershed, Campo Grande, Mato Grosso do Sul - Capoane, Viviane; Mescolotti, Patricia Colombo; Fushimi, Melina [UNESP]; Fontana, Ademir; Kuplich, Tatiana Mora; Silva, Daiane Alencar da (Revista Brasileira de Geomorfologia, 2024)
In this study, the arenization foci and areas undergoing arenization processes in the watershed of the Guariroba were mapped, investigating the genesis and morphodynamics of this arenization foci. Mapping was carried out using the Brightness Index 2 (BI2) based on Sentinel-2 satellite images. For classification, an image from the dry period (August 21, 2021) characterized by lower humidity and higher brightness was used. To validate the mapping, the BI2 from the rainy period (March 29, 2023), marked by higher humidity and lower brightness, was employed. BI2 was calculated in the SNAP software, and in ArcMap, the values were classified considering the histogram. The arenization foci cover an area of 238.6 hectares, and the areas undergoing arenization processes cover 919.1 hectares. The origin of this process is linked to the extensive removal of primary vegetation cover and conversion to agriculture, disregarding the natural fragility of Entisols (Quartzipsamments), which accelerated soil degradation. Over time, the degraded areas with exposed soil became more susceptible to erosive action from water and wind, resulting in the formation and expansion of arenization foci, occurring in different slope compartments. The findings emphasize the urgency of adopting soil and water conservation management practices. Such measures are essential to ensure the integrity of the ecosystem that provides 34% of the water supply for the city of Campo Grande/MS. The performance of BI2 was satisfactory; however, it is important to emphasize that achieving a realistic mapping of arenization foci requires not only theoretical proficiency but also field experience on the part of the classifier.
Detecção de focos de arenização na bacia hidrográfica do Córrego Guariroba, Campo Grande, Mato Grosso do Sul
Keywords: Environmental fragility; erosion susceptibility; inadequate management; land cover; land-use changes